Personal protective behaviors in response to COVID-19: a longitudinal application of protection motivation theory - Hinssen, Marina; Dohle, Simone (Frontiers in Psychology, 2023)
Introduction: Disease outbreaks are expected to occur more frequently and spread more rapidly in the age of globalization. Personal protective behaviors strongly affect infection and death rates worldwide. It is therefore of prime importance to better understand which factors predict personal protective behaviors during a pandemic. Protection motivation theory (PMT) proposes that people's motivation to protect themselves is based on two appraisal processes: threat appraisal and coping appraisal. Building on PMT, this longitudinal study aimed to predict personal protective behaviors in response to COVID-19, including hand hygiene, physical distancing, and mask wearing.In the first wave of the study (November 2020), the two appraisal processes as specified in PMT as well as intentions to perform protective behaviors were assessed in a representative sample of German adults (N = 328). In the second wave of this study, which was conducted one month later, the frequency of protective behaviors was measured.Structural equation modeling was used to test whether threat and coping appraisal predicted intentions and protective behaviors.Response rate for the second wave was high (87%). For all three behaviors, selfefficacy predicted intentions and also indirectly behavior (i.e., mediated via intentions).Furthermore, exploratory tests of alternative theoretical models suggested that both selfefficacy and costs have direct effects (i.e., independent from their relationship with intentions) on performed behavior.To support individuals to engage in protective beaviors during a pandemic, it is important to reduce barriers to action and to foster individuals' self-efficacy.